(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
Liquid-Crystalline Systems represent active compounds delivery systems that may be able to overcome the physical barrier of the skin, especially represented by the stratum corneum. To obtain these systems, aqueous and oily components are used with surfactants. Of the different association structures in such systems, the liquid-crystalline offer numerous advantages to a topical product. This manuscript presents the development of liquid-crystalline systems consisting, in which the oil component is olive oil, its rheological characterizations, and the location of liquid crystals in its phase map. Cytotoxic effects were evaluated using J-774 mouse macrophages as the cellular model. A phase diagram to mix three components with different proportions was constructed. Two liquid crystalline areas were found with olive oil in different regions in the ternary diagram with two nonionic surfactants, called SLC1 (S1) and SLC2 (S2). These systems showed lamellar liquid crystals that remained stable during the entire analysis time. The systems were also characterized rheologically with pseudoplastic behavior without thixotropy. The texture and bioadhesion assays showed that formulations were similar statistically (p < 0.05), indicating that the increased amount of water in S2 did not interfere with the bioadhesive properties of the systems. In vitro cytotoxic assays showed that formulations did not present cytotoxicity. Olive oil-based systems may be a promising platform for skin delivery of drugs.